On-demand, magnetic hyperthermia-triggered drug delivery: optimisation for the GI tract12. Issue 9 (11th February 2016) - Che Rose, Laili; Bear, Joseph C.; Southern, Paul; McNaughter, Paul D.; Piggott, R. Ben; Parkin, Ivan P.; Qi, Sheng; Hills, Brian P.; Mayes, Andrew G.
Abstract : An orally-administered vehicle for targeted on-demand delivery to the gastrointestinal tract is presented. Hyperthermia is induced from an external AC magnetic field to melt a super paramagnetic iron oxide nanoparticle wax composite coating and hence release the capsule content. Abstract : An orally-administered vehicle for targeted, on-demand drug delivery to the gastrointestinal (GI) tract is highly desirable due to the high incidence of diseases of that organ system and harsh mechanical and physical conditions any such drug delivery vehicle has to endure. To that end, we present an iron oxide nanoparticle/wax composite capsule coating that protects the capsule contents from the highly variable chemical conditions of the GI tract. It can be triggered using magnetic hyperthermia initiated from an external AC magnetic field. The coating is produced from pharmaceutically approved materials and is applied using a simple dip-coating process using a gelatin drug capsule as a template. We show that the coating is impervious to chemical conditions found within the GI tract, but is completely melted within two minutes of magnetically-induced heating under biologically-relevant conditions of temperature, pH, buffer and external field strength, allowing the delivery and dispersal of the capsule contents. The overall simplicity of action, durability and non-toxic and inexpensive nature of our drug delivery vehicle demonstrated herein are key for successful drug delivery systems for the kinds of focal therapy being sought for modern precision medicine.